The Tainted Shadow of the Green Revolution: The Cobalt Conundrum in the Democratic Republic of the Congo - Popławski, Błażej; Chymkowski, Roman (Stan Rzeczy, 2025)
The aim of this article is to characterise the system of the cobalt economy. The introduction presents the importance of cobalt for the green energy revolution. The production chain and the role of the main entities that co-create it are described. Then, the functioning of cobalt mines in the Democratic Republic of the Congo – including both large mines managed by corporations and artisanal small-scale ones – is discussed. Attention is drawn to phenomena such as forced labour, bonded labour, slave labour, child labour, the situation of women, and violations of all health and safety standards in mines. The article ends with an analysis of the effectiveness of international initiatives aimed at improving the situation of producers and implementing the idea of sustainable development.